High mobility and transparent ZTO ETM prepared by RF reactive co-sputtering for perovskite solar cell application - Islam M.A.; Rahman K.S.; Misran H.; Asim N.; Hossain M.S.; Akhtaruzzaman M.; Amin N. (Elsevier B.V., 2023)
Thin-films of Zinc Tin Oxide (ZTO) with high charge carrier mobility and superior optical transmittance has been prepared by the rf-reactive co-sputtering technique in argon-oxygen (99:01) ambient. These deposited films have been systematically studied to determine the effect of deposition temperature on film structure, composition, and optoelectronic properties. X-ray diffraction (XRD) spectra indicated that the ZTO films remain amorphous even growth temperature increased to 400 C. The films deposited at room temperature (RT) and 100 C were slightly tin-rich found in Energy-dispersive X-ray (EDX) spectroscopy compared to the films deposited over 100 C. It was found that growth temperature played a crucial role in carrier concentration and mobility of the films and such properties are controlled by the grain boundary scattering over the Sn dopant concentration. The transmittance of the films was found above 85% in the visible range regardless of substrate temperature. The complete perovskite solar cell has been numerically analyzed by employing SCAPS-1D software and the effect of ZTO's optoelectrical properties on cell performance has been revealed. 2019